The critical x[I/L]xbS motif in adaptor proteins, MAVS, MITA, and TRIF contributes to type I IFN production and antiviral immune response in fish - Xue Yun Peng; Jing Hou; Bo Li; Chuan Yun Zhang; Lin Huang; Lan Hao Liu; Nan Li; Pin Nie; Shan Nan Chen (Fish & Shellfish Immunology, 2026)

First molecular detection and partial ORF1 characterization of psittacine beak and feather disease virus (PBFDV) in domesticated parrots of Northern Vietnam - Hoang Minh; Brian Harvey Avanceña Villanueva; Quoc Khanh Dam; Lai Thi Lan Huong; Son Vu Nguyen; Dang Van Tan; Kuo-Pin Chuang (Archives of Virology, 2026)

Cyprinid herpesvirus 2 (CyHV-2) ORF53 inhibits NF-κB signalling by targeting p65 degradation - Chuan Yun Zhang; Zheng Liu; An Ning Pang; Jia Yi Li; Bo Li; Nan Li; Lan Hao Liu; Pin Nie; Shan Nan Chen (Fish & Shellfish Immunology, 2026)

Type I IFNs, IFNc, IFNd1, IFNd2, IFNh, and type II IFNs, IFN-γ and IFN-γrel, and their possible receptors with the identification of two variants of IFNc and IFNh in turbot (Scophthalmus maximus) - Bo Li; Meng Xin Yan; Yu Hang Deng; Xiao Qian Jiao; Shan Nan Chen; Xu Jia Zhang; Jia Le Chen; Xue Yun Peng; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2026)

Assessing the impact of climate variability on exposure indices of Portunid crabs in the Southern East China sea - Irene Chia Ling Lim; Yan-Lun Wu; Wei-Pin Hsu; Muhamad Naimullah; Wei-Yu Lee; Lu-Chi Chen; Kuo-Wei Lan (International Journal of Remote Sensing, 2026)

Projected impacts of climate change on the spatial distribution and habitat preference of tropical tuna in the Pacific Ocean - Yan-Lun Wu; Ting-Yu Liang; Wei-Pin Hsu; Teruhisa Shimada; Anindya Wirasatriya; Parichat Wetchayont; Chunhua Qiu; Kuo-Wei Lan (Marine Environmental Research, 2026)

Applying semi-supervised learning algorithms in real-environment solid waste classification - Dong–Ying Lan; Pin–Jing He; Hui–Huang Zou; Rong–Rong Kan; Yi Wang; Fan Lü; Hua Zhang (Resources, Conservation and Recycling, 2026)

Botulinum neurotoxin A alleviates Deinagkistrodon acutus venom-induced limb injury through promoting macrophage polarization in rabbits - Lutao Xie; Haohao Wu; Linjie Lai; Wang Du; Jiefeng Xu; Pin Lan (Toxicon, 2026)

Single-site mutation (M1058L) of feline infectious peritonitis virus (FIPV) spike protein in domestic cats of Northern Vietnam - Quang Hong Duong; Thi Lan Huong Lai; Brian Harvey Avanceña Villanueva; Hoang Minh; Kuo-Pin Chuang (Archives of Virology, 2026)

MHC II system of mandarin fish (Siniperca chuatsi): Gene identification, expression analysis and transcriptional regulation - Jing Hou; Lu Qi; Ran Cao; Lan Hao Liu; Shan Nan Chen; Pin Nie (Aquaculture, 2026)

Characterization of monoclonal antibody against IgM and phagocytic function of IgM+ B cells in snakehead (Channa argus) - Peng Fei Mu; Zhe Wang; Qi Li; Qiu Hua Li; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2026)

Genomic, transcriptional and proteomic clarification of fathead minnow and common carp composition in epithelioma papulosum cyprini (EPC) cell line - Bo Li; Jing Hao Yuan; Yu Hang Deng; Shan Nan Chen; Meng Yao Ji; Xu Jia Zhang; Yang Liu; Zhen Gan; Pin Nie; Lan Hao Liu (Fish & Shellfish Immunology, 2026)

Effects of Shifts in Bacterial Community on Improving Water Quality and Growth Performance of Pacific Whiteleg Shrimp (Litopenaeus vannamei) in Biofloc Systems - Hai-Hong Huang; Chao Cheng; Li-Li Guo; Wan-Sheng Zou; Yan-Ju Lei; Wei-Qi Kuang; Bo-Lan Zhou; Pin-Hong Yang; Chao-Yun Li (Fishes, 2025)
This study aimed to induce a shift in a bacterial community by adding substrate into a biofloc system to characterize this shift and estimate its benefits in improving water quality and aquatic animal growth. We compared the bacterial communities between two biofloc systems, either with (sB treatment) or without (nB treatment) the addition of substrate (elastic solid packing filler), and we also analyzed the effects of the shift on the water quality and growth performance of shrimp (Litopenaeus vannamei). Beta diversity analysis indicated that the bacterial communities in the two treatments were significantly different (Jaccard index 0.94 ± 0.01, pseudo-F = 3.96, p = 0.001). The addition of substrate showed significant positive effects on bacterial alpha diversity indices (Shannon, Heip, Pielou, and Simpson; p

A point-of-care testing biosensing platform integrated with physiologically based pharmacokinetic model for on-site therapeutic drug monitoring of methotrexate - Feng-Feng Zhang; Mei-Juan Wu; Zi-Wei Yu; Yi-Lan Lin; Pin-Fang Huang; Meng-Meng Liu (Chemical Engineering Journal, 2025)

Genome-wide identification, expression analysis and transcriptional regulation of major histocompatibility complex class I genes in mandarin fish Siniperca chuatsi - Jing Hou; Min Chang Li; Lu Qi; Wei Hao; Lan Hao Liu; Zhen Gan; Bei Huang; Wen Shu Huang; Li Wang; Li Li; Shan Nan Chen; Pin Nie (Aquaculture, 2025)

Cardiovascular dysfunction and altered lysosomal signaling in a murine model of acid sphingomyelinase deficiency - Yun-Ting Wang; Alexandra K. Moura; Rui Zuo; Kiana Roudbari; Jenny Z. Hu; Saher A. Khan; Zhengchao Wang; Yangping Shentu; Mi Wang; Pin-Lan Li; Jiukuan Hao; Yang Zhang; et al. (Journal of Molecular Medicine, 2025)

Molecular characterization of TRAF gene family in snakehead (Channa argus) - Xiu Feng Han; Ming Yue Che; Xue Su; Jing Yun Tian; Lan Hao Liu; Pin Nie; Su Wang (Fish & Shellfish Immunology, 2025)

Parafrigoribacterium soli sp. nov. and Parafrigoribacterium humi sp. nov., two novel siderophore-synthesizing species isolated from black soil - Yu-Ting OuYang; Le-Bin Chen; Jian-Yu Jiao; Zi-Xuan Hu; Jiong-Shan Wang; Tian-Hang Yang; Jun Xiao; Ting-Ting She; Pin-Jiao Jin; Shuang Wang; Lan Liu; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

Novel method for predicting concentrations of incineration flue gas based on waste composition and machine learning - Ya-Ping Qi; Pin-Jing He; Dong-Ying Lan; Fan Lü; Hua Zhang (Journal of Environmental Management, 2025)

Rapid detection of colored and colorless macro- and micro-plastics in complex environment via near-infrared spectroscopy and machine learning - Hui-Huang Zou; Pin-Jing He; Wei Peng; Dong-Ying Lan; Hao-Yang Xian; Fan Lü; Hua Zhang (Journal of Environmental Sciences, 2025)

Unveiling the non-linear effects of water and oil on hyperspectral imaging-based characterization of solid waste by hyperspectral unmixing - Dong-Ying Lan; Pin-Jing He; Ya-Ping Qi; Fan Lü; Hua Zhang (Waste Management, 2024)

Inhibitory effects of cold plasma-activated water on the generation of advanced glycation end products and methylimidazoles in cookies and mechanistic evaluation using electron paramagnetic resonance - Chenxia Zhang; Jian Zhang; Tiantian Huang; Pin Jiang; Xuejiao Qie; Lan Mo; Maiquan Li; Aihua Lou; Qingwu Shen; Jie Luo; Shuai Wang; Yi XueC; et al. (Food Chemistry, 2024)

Methylobacterium nigriterrae sp. nov., isolated from black soil - Le-Bin Chen; Yu-Ting OuYang; Lan Liu; Pin-Jiao Jin; Rong-Rong Huang; Wen-Yi Pan; Ying Wang; Jia-Ying Xing; Ting-Ting She; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Possible toxification mechanisms of acute and chronic pentachlorophenol to Montipora digitata: Limitation of energy supply and immunotoxicity - Lan Luo; Pengfei Xue; Xuan Chen; Pin Gan; Xiaoli Li; Kefu Yu; Yuanyuan Zhang (Science of The Total Environment, 2024)

SIRT6 positively regulates antiviral response in a bony fish, the Chinese perch Siniperca chuatsi - Xiang Yang Wu; Zhi Wei Zhang; Shan Nan Chen; An Ning Pang; Xue Yun Peng; Nan Li; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2024)

Production and characterization of seaweed-based bioplastics incorporated with chitin from ramshorn snails - Regina Zhi Ling Leong; Swee Sen Teo; Hui Yin Yeong; Swee Pin Yeap; Phei Er Kee; Su Shiung Lam; John Chi-Wei Lan; Hui Suan Ng (Systems Microbiology and Biomanufacturing, 2024)

The establishment and evaluation of a swine model of deinagkistrodon acutus snakebite envenomation - Linjie Lai; Lutao Xie; Yi Chen; Wang Du; Xuelin Yang; Wanjuan Liu; Peixin Shangguan; Jiefeng Xu; Pin Lan (Toxicon, 2024)

Assessment of sediment transport in Luxiapuqu watershed using RUSLE-TLSD and InSAR techniques: Yarlung Tsangpo River, China - Hao-Shuang Chen; Ling Lan; Yi-Pin Nie; Yu-Ge Wang; Xie-Kang Wang (Environmental Science and Pollution Research, 2024)

Exposure to pentachlorophenol destructs the symbiotic relationship between zooxanthellae and host and induces pathema in coral Porites lutea - Yuanyuan Zhang; Lan Luo; Pin Gan; Xuan Chen; Xiaoli Li; Yan Pang; Xiaopeng Yu; Kefu Yu (Science of The Total Environment, 2024)

Branch distribution pattern and anticoagulant activity of a fucosylated chondroitin sulfate from Phyllophorella kohkutiensis - Di Lan; Jiali Zhang; Xiaolei Shang; Lijuan Yu; Chen Xu; Pin Wang; Lige Cui; Nanqi Cheng; Huifang Sun; Jianing Ran; Le Sha; Ronghua Yin; et al. (Carbohydrate Polymers, 2023)

Inactivation of Heterosigma akashiwo under UV/peroxydisulfate advanced disinfection system in marine waters - Xuan Chen; Kunling Huang; Pin Gan; Lan Luo; Kefu Yu; Yuanyuan Zhang; Yunfeng Pang; Pengfei Xue (Chemosphere, 2023)

Molecular cloning and functional analysis of polymeric immunoglobulin receptor, pIgR, gene in mandarin fish Siniperca chuatsi - Jia Xiang Ji; Lin Zhang; Li Li; Kai Lun Wang; Jing Hou; Lan Hao Liu; Bo Li; Bai Dong Zhang; Nan Li; Shan Nan Chen; Pin Nie (Fish & Shellfish Immunology, 2023)

Effects of Bacillus strain added as initial indigenous species into the biofloc system rearing Litopenaeus vannamei juveniles on biofloc preformation, water quality and shrimp growth - Hai-Hong Huang; Chao-Yun Li; Yan-Ju Lei; Bo-Lan Zhou; Wei-Qi Kuang; Wan-Sheng Zou; Pin-Hong Yang (Aquaculture, 2023)

Oceanobacillus saliphilus sp. nov., Isolated from Saline−Alkali Soil in Heilongjiang Province, China - Yu-Ting OuYang; Meng-Meng Li; Ai-Ping Lv; Pin-Jiao Jin; Lan Liu; Ze-Tao Liu; Jian-Yu Jiao; Wen-Jun Li; Li-Xiang Cao; Shuang Wang (Current Microbiology, 2022)

Bioactivity-guided isolation of compounds from Sophora flavescens with antibacterial activity against Acinetobacter baumannii - Pin Li; Wern Chern Chai; Zhan-Yi Wang; Kai-Jun Tang; Jin-Yao Chen; Henrietta Venter; Susan J. Semple; Lan Xiang (Natural Product Research, 2022)

Effect of gradation variation on particle transport process in a generalized flash flood gully via CFD-DEM method - Yi-pin Nie; Ling Lan; Xu-feng Yan; Xie-kang Wang (Acta Geophysica, 2022)

Pathogenic characterization of Aeromonas salmonicida subsp. masoucida turbot isolate from China - Ping Wang; Jie Li; Tian Tian He; Nan Li; Zhao Lan Mo; Pin Nie; Hai Xia Xie (Journal of Fish Diseases, 2020)
Aeromonas salmonicida is a gram‐negative bacterium that is the causative agent of furunculosis. An A. salmonicida strain was isolated from diseased turbot ( Scophthalmus maximus ) with the sign of furunculosis from North China. Based on vapA gene, the strain was further classified as A. salmonicida subsp. masoucida RZ6S‐1. Culturing RZ6S‐1 strain at high temperature (28°C) obtained the virulence attenuated strain RZ6S. Genome sequence comparison between the two strains revealed the loss of the type IV secretion system (T4SS) and type III secretion system (T3SS) from the native plasmid pAsmB‐1 and pAsmC‐1 of wild‐type strain RZ6S‐1, respectively. Further study demonstrated that the wild‐type strain RZ6S‐1, but not its derivative mutant RZ6S, can stimulate apoptosis. Elevated protein level of cleaved caspase‐3 was detected from epithelioma papulosum cyprinid (EPC) cells infected with wild‐type strain RZ6S‐1 as compared with that infected with RZ6S strain. Meanwhile, the invasion of the mutant strain RZ6S was about 17‐fold higher than the wild‐type strain RZ6S‐1, suggesting that some protein(s) from A. salmonicida subsp. masoucida RZ6S‐1 suppress its invasion. The RZ6S mutant strain was attenuated, since its LD 50 is over 10,000 times higher compared to the wild‐type strain as revealed in the turbot infection model.

Contribution of redox-dependent activation of endothelial Nlrp3 inflammasomes to hyperglycemia-induced endothelial dysfunction - Yang Chen; Lei Wang; Ashley L. Pitzer; Xiang Li; Pin-Lan Li; Yang Zhang (Journal of Molecular Medicine, 2016)

Acid sphingomyelinase inhibition protects mice from lung edema and lethal Staphylococcus aureus sepsis - Huiming Peng; Cao Li; Stephanie Kadow; Brian D. Henry; Jörg Steinmann; Katrin Anne Becker; Andrea Riehle; Natalie Beckmann; Barbara Wilker; Pin-Lan Li; Timothy Pritts; Michael J. Edwards; et al. (Journal of Molecular Medicine, 2015)

Transplantation of mesenchymal stem cells into the renal medulla attenuated salt-sensitive hypertension in Dahl S rat - Junping Hu; Qing Zhu; Min Xia; Tai L. Guo; Zhengchao Wang; Pin-Lan Li; Wei-Qing Han; Fan Yi; Ningjun Li (Journal of Molecular Medicine, 2014)

Control of autophagy maturation by acid sphingomyelinase in mouse coronary arterial smooth muscle cells: protective role in atherosclerosis - Xiang Li; Ming Xu; Ashley L. Pitzer; Min Xia; Krishna M. Boini; Pin-Lan Li; Yang Zhang (Journal of Molecular Medicine, 2014)

Nod-Like Receptor Protein 1 Inflammasome Mediates Neuron Injury under High Glucose - Xian-Fang Meng; Xiao-Lan Wang; Xiu-Juan Tian; Zhi-Hua Yang; Guang-Pin Chu; Jing Zhang; Man Li; Jing Shi; Chun Zhang (Molecular Neurobiology, 2014)

Protective role of growth hormone against hyperhomocysteinemia-induced glomerular injury - Caixia Li; Min Xia; Justine M. Abais; Xiaocheng Liu; Ningjun Li; Krishna M. Boini; Pin-Lan Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

TRAIL death receptor 4 signaling via lysosome fusion and membrane raft clustering in coronary arterial endothelial cells: evidence from ASM knockout mice - Xiang Li; Wei-Qing Han; Krishna M. Boini; Min Xia; Yang Zhang; Pin-Lan Li (Journal of Molecular Medicine, 2013)

Epithelial-to-mesenchymal transition in podocytes mediated by activation of NADPH oxidase in hyperhomocysteinemia - Chun Zhang; Min Xia; Krishna M. Boini; Cai-Xia Li; Justine M. Abais; Xiao-Xue Li; Laura A. Laperle; Pin-Lan Li (Pflügers Archiv - European Journal of Physiology, 2011)

Rescue of Newcastle disease virus from cloned cDNA using an RNA polymerase II promoter - Bao-yu Li; Xue-rui Li; Xi Lan; Xiang-pin Yin; Zhi-yong Li; Bin Yang; Ji-xing Liu (Archives of Virology, 2011)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)